2012
DOI: 10.1098/rstb.2012.0233
|View full text |Cite
|
Sign up to set email alerts
|

Warming and nitrogen affect size structuring and density dependence in a host–parasitoid food web

Abstract: Body size is a major factor constraining the trophic structure and functioning of ecological communities. Food webs are known to respond to changes in basal resource abundance, and climate change can initiate compounding bottom-up effects on food-web structure through altered resource availability and quality. However, the effects of climate and co-occurring global changes, such as nitrogen deposition, on the density and size relationships between resources and consumers are unknown, particularly in host-paras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 39 publications
5
43
1
Order By: Relevance
“…In a field manipulation of the temperature and nitrogen load experienced by a host-parasitoid food web, however, increasing temperature or nitrogen yielded higher host densities and consequently more generalized feeding by parasitoids. Interestingly, increasing temperature and nitrogen simultaneously did not yield an additive response in host density or parasitoid generality, suggesting that they do not interact linearly [20]. Differences in whether warming counteracts enrichment [17] or if both effects are non-additive [20] may be explained by the presence of a strongly size-structured predator -prey community in the aquatic experiment of the former and the lack thereof in the host-parasitoid community of the latter study as suggested by model analyses [11].…”
Section: Warming and Bottom-up Controlmentioning
confidence: 85%
See 2 more Smart Citations
“…In a field manipulation of the temperature and nitrogen load experienced by a host-parasitoid food web, however, increasing temperature or nitrogen yielded higher host densities and consequently more generalized feeding by parasitoids. Interestingly, increasing temperature and nitrogen simultaneously did not yield an additive response in host density or parasitoid generality, suggesting that they do not interact linearly [20]. Differences in whether warming counteracts enrichment [17] or if both effects are non-additive [20] may be explained by the presence of a strongly size-structured predator -prey community in the aquatic experiment of the former and the lack thereof in the host-parasitoid community of the latter study as suggested by model analyses [11].…”
Section: Warming and Bottom-up Controlmentioning
confidence: 85%
“…Interestingly, increasing temperature and nitrogen simultaneously did not yield an additive response in host density or parasitoid generality, suggesting that they do not interact linearly [20]. Differences in whether warming counteracts enrichment [17] or if both effects are non-additive [20] may be explained by the presence of a strongly size-structured predator -prey community in the aquatic experiment of the former and the lack thereof in the host-parasitoid community of the latter study as suggested by model analyses [11]. Interestingly, the size structure of host-parasitoid communities may be strengthened by warming [18,20], which may modify interactions with enrichment.…”
Section: Warming and Bottom-up Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, only two recent studies from subtropical Australia have addressed this topic and found a decrease of parasitism with elevation [18,46], which we support. Higher parasitism at lower and warmer lower elevation might be caused by higher attack rates of parasitoids, as demonstrated in controlled warming experiments [60]. Thus, increasing temperatures with climatic change will probably increase parasitism rates but influence host-parasitoid interactions in unpredictable ways, as it is unclear if hosts and parasitoids will react similarly [5].…”
Section: (C) Influence Of Elevation On Host-parasitoid Interactionsmentioning
confidence: 97%
“…Interestingly, studies in this issue on both theoretical predator-prey systems [38] and empirical litter feeding arthropod communities [39] predict changes in diet breadth as a result of changes in foraging behaviour in response to climate change, indicating the potential generality of these effects. While our predictions are based on weather variability, de Sassi et al [40] demonstrate that changes in mean temperature and nitrogen deposition can also lead to changes in electivity. Both these factors affect host density, which should lead to a higher host encounter rate for parasitoids, making it more likely that they will be egg-limited and therefore more elective.…”
Section: Discussionmentioning
confidence: 86%